URGENSI PENEGAKAN TERHADAP PENCEMARAN LINGKUNGAN HIDUP DALAM ASPEK HUKUM PIDANA - Andoko Andoko (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2023)
So far, academics and practitioners are quite familiarwith the term environmental law, which in Indonesian is known asthe rule of law. Referring to the type of government that the statebased on law is a general idea or concept that is not related to anyparticular field of law. Even though the study of why environmentallaw is needed is very focused on the impact of environmental damagecausedbymassiveexploitationinordertofulfilleconomicdevelopment. As a caliph on earth, it is appropriate for humans toprotect and care for the earth and everything in it. However, in aneffort to improve the quality of life, humans try their best to processandutilizenaturalresources.Environmentalexploitationalsoinvolves the private sector on behalf of companies or corporations.The stagnation of law enforcement efforts by prioritizing criminalsanctionshasresultedinafeelingofdeterrenteffecthavingdisappeared and the law as if it is not obeyed by the perpetrators ofenvironmentalcrimes,becausethisresearchfocusesmoreonstudying environmental criminal law related to the aspect of urgencyprioritizing criminal sanctions against perpetrators ofenvironmentalcrimes life. This study uses a normative research model, researchbased on analyzing legal principles, norms and all regulations thatapply in the legal system in Indonesia related to the environment.This normative research will analyze laws and regulations and tostrengthen the results of the research the authors use xample as areinforcement of research results. The results of this study indicatethat the application of criminal sanctions has a high urgency, becausecriminal sanctions havea deterrent effect.